PENGALAMAN SPIRITUAL MAHASANTRI PONDOK PESANTREN MAHASISWA PONOROGO - Yusuf Hamdani Abdi; Afitria Rizkiana; Panuju Panuju (TARBAWI:Journal on Islamic Education, 2021)
Islamic boarding school is an Islamic Education institution that presents people of faith and pious. Islamic boarding schools have students who are referred to as santri. Students in Islamic boarding schools are mahasantri. One month educational change program at the Islamic Boarding School at Muhammadiayah University, Ponorogo. The general objective of this research is to describe the spiritual experiences of boarding school mahasantri students, the specific objectives for 1. finding the experiences of boarding school student spirituality. 2. The existence of mahasantri in Islamic boarding schools. 3. Supporting factors of student life in Islamic boarding schools. This research uses descriptive phenomenological design with in-depth interview method. The informants consisted of 2 male and 3 female students. The results of the study found facts during the boarding school changed vertical and horizontal spiritual experiences. Vertical spiritual experience is the experience of the Informant's relationship with the creator god. Horizontal spiritual experience represents the experience of interacting with the environment and people around. The informant's vertical experience of feeling of faith becomes more intensive. The horizontal spiritual experience of the informant doing various activities becomes more sincere because of Allah SWT. The meaning obtained from spiritual experience. Spiritual experiences convey a sense of satisfaction and happiness, self-confidence arises after successfully completing personal and other people's efforts. The following are life supporting factors in Islamic boarding schools, namely: (1) Mahasantri's visit to Islamic boarding school. (2) The benefits felt by students in boarding schools. The results of this study can help administrators of student boarding schools in understanding the needs of students.